RELATIONSHIPS BETWEEN PRINCIPALS’ COMMUNICATION STYLES AND ADMINISTRATIVE EFFECTIVENESS IN PUBLIC SECONDARY SCHOOLS IN ANAMBRA STATE (UNIZIK Journal of Educational Management and Policy, 2025)
The need for administrative effectiveness in secondary school systems in Anambra State to ensure quality and prompt delivery of educational services cannot be over-emphasized. This prompted the researchers to determine the relationship between principals’ communication styles and administrative effectiveness in public secondary schools in Anambra State. Two research questions guided the study and two hypotheses were tested at. 05 level of significance. Correlation research design was adopted for the study. The population was 5,214 participants comprising 264 principals and 4,950 teachers in public secondary schools in Anambra State. Proportionate stratified random sampling technique was used to draw the sample for study. Structured questionnaires were used for data collection. The instruments were face and construct validated. The researcher administered 285 copies of the instruments were administered to the respondents with the help of two research assistants using direct method and retrieval and 280 copies were retrieved. Data were analyzed using Pearson Product Moment Correlation Coefficient while the p-value was used to determine the significance of relationship at 0.05 significant levels for all hypotheses. The results among others revealed that principals agreed that there is very high positive relationship between result-driven communication style and administrative effectiveness in public secondary schools in Anambra. Accordingly, it was recommended among others that efforts should be made to encourage principals to adopt result-driven communication style so as to improve on their administrative effectiveness.